Exploring the role of accounting history following the adoption of IFRS in Europe. The case of Italy - Paglietti, Paola (De Computis, Revista Española de Historia de la Contabilidad., 2009)
The mandatory adoption of the International Financial Reporting Standards (IFRS), enforced by Regulation (EC) No. 1606/2002, may be particularly upsetting in the European countries with strong traditions of accounting theory and regulation. This paper presents an investigation that stresses the importance of previous accounting solutions which were developed nationally to face the challenge of adopting an exogenously developed set of international accounting standards, such as IFRS, in the current EU setting. The research focuses on Italy and reviews the “patrimonial” accounting approach developed in the 1880s by Fabio Besta (1845-1922), an Italian scholar who is unanimously considered to be the initiator of the modern accounting theory in Italy. His approach was in use in Italy until the 1970s, after which the approach of another scholar, Gino Zappa (1879-1960), has been followed. Fabio Besta shifted from a personalistic to a materialistic (or nonpersonalistic) theory of accounts. He put forward new ideas quite similar in many respects to the modern AngloAmerican theoretical approaches to accounting (Zambon, 2001; Viganò and Mattessich, 2007). The “patrimonial” accounting theory focuses on the firm’s wealth, as reflected in the balance sheet, and on its valuation. It evokes the so-called “asset and liability view”, which is the approach used by several standardsetting bodies, e.g. FASB and IASB, to develop conceptual frameworks (Johnson, 2004). Such an approach defines the objective of financial statements as providing information on the firm’s financial position interpreted as the firm’s wealth. Assets and liabilities are defined as resources and obligations and are regarded to be the primary indicators of the wealth of a firm. Revenues and expenses are indirectly defined in terms of changes in assets and liabilities (Sprouse and Moonitz, 1962). Accordingly, income measures the increase or decrease in the firm’s wealth (FASB, 1976). This paper begins with an analysis of Besta’s theory, and then proceeds to compare Besta’s theory with the IFRS conceptual framework and measurement criteria, showing several similarities. In particular, it emerges that both approaches are built on the same theoretical foundations, namely the “patrimonial” accounting perspective and the atominstic-reductionist view of the firm’s wealth. In conclusion, this study appraises anew Fabio Besta’s thought in the age of IFRS. His theoretical perspectives might help to understand better and thereby more effectively evaluate the present accounting context, such to possibly favour a better contribution from contemporary accounting researchers in the new international scenario where accounting standards have been developing.